Indicadores metabólicos para identificação de genótipos de algodoeiro tolerantes a salinidade - Marcelino, Aline Dayanna Alves De Lima (2023)
Salinity is a global abiotic stress that affects crop development and production. When the saline concentration of the soil exceeds the limits relative to each threshold salinity range of crops, the adverse osmotic and ion-specific effects of salt absorption directly affect plant metabolism, inhibiting water absorption by reducing pressure. external osmotic. As a consequence, physiological and biochemical changes occur in plant cells. To avoid damage, tolerant species trigger several response mechanisms, balancing the osmotic adjustment, presenting abilities that prevent, through regulation, excessive amounts of salts from reaching the protoplasm, thus tolerating the resulting toxic and osmotic effects. Knowledge of sources of resistance to unfavorable conditions is important for use in crop genetic improvement programs. In this sense, the present work aimed to evaluate commercial cotton cultivars to identify salinity tolerance based on physiological and biochemical analyses. Eleven commercial cotton cultivars adapted to the Cerrado (savannah) and semi-arid environments were grown in a greenhouse in Campina Grande (BRS Seridó, BRS 286, FM966, CNPA 7MH, FMT 701, CNPA ITA 90, FMT 705, BRS Rubi, BRS 416, MT 152, BRS Acácia). The design was in randomized blocks, with three replications, in a factorial scheme, using 11 cotton genotypes and two treatments (with and without salt), Control and Stress - represented by watering with normal water (0.3 dS m-1) and saline (10 dS m-1), for 34 days. The saline solution (NaCl) was prepared following the relationship between the electrical conductivity of water (ECa) and salt concentrations (10*meq L-1 = 1 dS m-1 ECa). Plant growth was monitored and gas exchange was evaluated with the aid of IRGA (Infrared Gas Analyzer), chlorophyll a fluorescence with the aid of a pulse modulated fluorometer device (OS5p - Opti Science), enzyme activity antioxidants and free proline, made from crude extracts of total protein (25%). As a result, we identified that salinity impacted plant growth, reflected in the data on gas exchange and free proline in most cultivars, however, BRS 286, FMT 705, BRS 416 and BRS Acácia and CNPA 7MH exhibited the ability to overcome the effect of stress and adjust osmotically, therefore minimizing damage to growth. It was observed that the BRS Acácia and FMT 701 cultivars adequately activated the antioxidant enzyme machinery, in order to favor their defense process during the period of salt stress. In terms of fluorescence, both reduced the initial fluorescence, indicating better photosynthetic efficiency. BRS Acácia, however, outperformed in osmotic adjustment, based on total proline which reached 40% in stressed plants. With this adjustment, the plants suffered less from the impact of salt stress, demonstrated by less cellular wear for polyphenol production during severe stress. Regarding the elimination of the peroxyl radical, it was found that BRS Acácia and FMT 701 sequestered 20% and 40%, respectively, indicating that the latter had lower antioxidant activity.